Changes of the internalisation of the values of elder schoolchildren - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2002)
In this paper we analyse the changes in the internalization of the values of the elder age schoolchildren. Comparing changes in the cognitive level of the internalisation of the values of the students who attended the tenth and eleventh year in 1998 and 2001. Based on the data of this scientific research, we first present the past changes in the pitch spiritual values of these students. Then we show how they changed their views on moral values, aesthetic, religious, social and others. It also provides motivation for the meaning of the changes of these values.
Keywords: Moral education; values; internalization; elder schoolchildren.